Association between frailty, as measured by the FRAIL scale, and 1-year mortality in older patients undergoing hip fracture surgery - Shaohua Xi; Zhibin Wu; Jian Cui; Suran Yin; Shaozhi Xi; Chaoyang Liu (BMC Geriatrics)
Abstract Background The FRAIL scale is a concise and user-friendly tool for frailty assessment. However, its effectiveness in predicting 1-year mortality among older patients undergoing hip fracture surgery remains unclear. This study explored the relationship between preoperative frailty, as measured by the FRAIL scale, and 1-year mortality after surgery in this population. Methods This retrospective analysis included 194 older patients (aged ≥ 75 years) with hip fractures who underwent surgical treatment in our departments from January 2019 to December 2022. Perioperative clinical data were collected, and all-cause mortality within 1 year after surgery was monitored. Patients were categorized into non-frail (n = 114) and frail (n = 80) groups based on their FRAIL scores. Postoperative complications and 1-year mortality rates were compared between these groups. The association of preoperative frailty with 1-year mortality and its predictive capability were assessed. Results Among the 194 older hip fracture patients, 78 (40.2%) were male, with a mean (standard deviation [SD]) age of 84.4 (6.3) years. The overall incidence of 1-year mortality after surgery was 11.3% (22/194). Frail patients had a higher incidence of Clavien-Dindo (CD) classification of surgical complications ≥ II (31.3% vs. 12.3%, p = 0.00) and greater 1-year mortality (21.3% vs. 4.4%, p = 0.00) compared with non-frail patients. Cox regression analysis indicated that preoperative frailty was independently associated with 1-year mortality (adjusted hazard ratio: 3.88; 95% confidence interval [CI]: 1.28–11.77; p = 0.02). The FRAIL scale demonstrated acceptable discriminatory capacity for predicting 1-year mortality in these patients (area under the curve: 0.70; 95% CI: 0.59–0.81). Conclusions Frailty, as measured by the FRAIL scale, was independently associated with 1-year mortality in older patients undergoing hip fracture surgery. The scale can be used to stratify risk and facilitate personalized perioperative treatment and management.